2021
DOI: 10.1021/acs.jpcb.1c02398
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SARS-CoV-2 Receptor Binding Domain with Stapled Peptides: An In Silico Study

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has evolved into a pandemic of unprecedented scale. This coronavirus enters cells by the interaction of the receptor binding domain (RBD) with the human angiotensin-converting enzyme 2 receptor (hACE2). In this study, we employed a rational structure-based design to propose 22-mer stapled peptides using the structure of the hACE2 α1 helix as a template. These peptides were designed to retain the α-helical character of the natural structure, to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 82 publications
(199 reference statements)
0
18
0
Order By: Relevance
“… 62 Interestingly, stapled peptides have also been designed that target the RBD of the SARS-CoV-2, which upon analysis through MD simulations and binding free energy calculations has been shown to bind with a potency that is similar to that of experimentally proven peptide inhibitors. 63 …”
Section: Drug Design and Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“… 62 Interestingly, stapled peptides have also been designed that target the RBD of the SARS-CoV-2, which upon analysis through MD simulations and binding free energy calculations has been shown to bind with a potency that is similar to that of experimentally proven peptide inhibitors. 63 …”
Section: Drug Design and Discoverymentioning
confidence: 99%
“…A similar work studied the effect of small molecules SSAA09E2 and Nilotinib on the ACE2-RBD interface through MD simulations and found that they intervene with hydrogen bonds at the interface and hence the flexibility of the proteins . Interestingly, stapled peptides have also been designed that target the RBD of the SARS-CoV-2, which upon analysis through MD simulations and binding free energy calculations has been shown to bind with a potency that is similar to that of experimentally proven peptide inhibitors …”
Section: Drug Design and Discoverymentioning
confidence: 99%
“…The MM-GBSA binding free energy was estimated according to the formula: ΔGbind = Gcomplex – Greceptor – Gligand, where ΔGbind is the binding free energy and Gcomplex, Greceptor, and Gligand are the free energies of the complex, receptor, and ligand, respectively. MM-GBSA values were obtained from the script of thermal MM-GBSA provided by Schrödinger ( https://www.schrodinger.com/scriptcenter ) and were used to calculate the ΔGbind for the protein–ligand complexes [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…De Campos et al [ 36 ] employed rational structure‐based design to propose 22‐mer stapled peptides using the structure of the hACE2 Helix 1, as a template. In this in silico approach, the researchers used different types of molecular configurations to construct the chemical linkers: lactam bridge, double lactam bridge, and alkene link (Figure 4 ).…”
Section: Stapled Peptides As Inhibitors Of Host Cell Entry By Sars‐co...mentioning
confidence: 99%